The Effect of Forced Choice on Choice - Dhar, Ravi; Simonson, Itamar (Journal of Marketing Research, 2003)
Whereas most academic and industry studies of consumer preferences and decision making involve forced choice (i.e., participants are told to choose one of the presented product or service alternatives), buyers usually also have the option not to select any alternative. An implicit assumption in the experimental practice of forcing choice is that the no-choice option draws proportionately from the various available alternatives, such that the qualitative conclusions are unaffected. However, the authors propose that the no-choice option competes most directly with alternatives that buyers tend to select when they are uncertain about their preferences. Building on this general proposition, the authors show that the introduction of the no-choice option strengthens the attraction effect, weakens the compromise effect, and decreases the relative share of an option that is “average” on all dimensions. They also examine the mechanisms underlying the impact of having the option not to choose and the conditions under which the no-choice option is likely to affect relative option shares. The results are consistent with the notion that the no-choice option provides an alternative way of resolving difficult choices that is not available when subjects are forced to choose. The authors discuss the theoretical and practical implications of this research.